(untitled) (Bangladesh Journal of Microbiology, 2016)
Pathogenic Escherichia coli remain an important etiological agent of infantile diarrhea in Bangladesh. Present study focused on the features of E. coli strains isolated from clinical and environmental samples. A total of 6 surface water samples and 6 clinical samples were examined. Isolates were analyzed on the basis of colony morphology and biochemical traits. The antibiogram profile of the isolates was determined against 6 commonly used antibiotics. Ten isolates were found to be resistant against more than 1 antibiotic. Both types of isolates showed 50% resistance against trimethoprim-sulfamethoxazole. Clinical isolates showed 100% sensitivity against gentamicin whereas 2 environmental isolates were found to be resistant against the antibiotic. Eighty and sixty five percent of environmental strains were sensitive against ceptriaxone and ciprofloxacin, respectively; while 50% showed resistance against ampicillin and nalidixic acid. In case of clinical strains, 65% isolates were found to be sensitive against ceptriaxone whereas 65% showed resistance against ampicillin and nalidixic acid; and 50% isolates were found to be resistant against ciprofloxacin. The isolates (n=12) were also examined for the presence of plasmids conferring the antibiotic resistance. However, no such plasmid was observed. Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 44-48